EFESIENSI PEMASARAN KOPI ARABIKA DI CV. ABIAN KECAMATAN KINTAMANI, KABUPATEN BANGLI - I Ketut Arnawa; Luh Putu Kirana Pratiwi; Erbiati Gono Ate (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research is entitled Marketing Efficiency of Arabica Coffee at CV Abian Kec. Kintamani Arabica coffee is a product that is certified for geographical indications so that it has a wide marketing distribution that is traded all over the world. The purpose of the study to analyze 1. marketing costs, marketing margins, farmer share, 2. Marketing efficiency. The analysis methods used include marketing margin analysis, farmer share analysis, marketing efficiency analysis The location of the research was conducted in CV abian. Kec. Kintamani Respondents in this study were determined as many as 30 respondents, 5 collectors, 2 retailers, and 5 consumers. Based on the results of the study, 3 marketing channels were found, with details in the level I marketing channel no marketing costs and margins (0), farmer share 100%, and marketing efficiency 0.00%. In the level II marketing channel, marketing costs (Rp 536/kg), marketing margin (Rp 1,200/kg), farmer share 95%, marketing efficiency 0.02%, while in the level III marketing channel, marketing costs (Rp 3,400/kg), farmer share 88%, marketing efficiency 0.10%. From the three marketing channels found, it can be concluded that the most efficient marketing channel is the level I channel. It is hoped that all Arabica coffee farmers in the research area will pay more attention to the marketing of Arabica coffee so that it can be even better in the future